Empowering Leadership Dalam Peningkatan Kreativitas Karyawan - Santi Retno Sari; Kumba Digdowiseiso (Jurnal Kajian Ilmiah, 2022)
The purpose of this study is to examine empowerment leadership and its dimensions, namely the dimensions of leading by example, coaching, participative decision making, informing and show concern and also include creative self-efficacy variables in influencing employee creativity. The study took the population of employees at three companies in the field of financial services located in Jakarta. The sample measurement technique uses the Slovin formula. From this calculation, a sample size of 159 employees was obtained. Intake of 159 samples taken by simple random sampling technique. The data analysis technique used to test the hypothesis was using multiple regression with SPSS 26. The results showed that increasing the practice of empowering leadership and creative self-efficacy of employees will increase employee creativity. The results of the influence of the five dimensions of empowerment leadership on employee creativity, only the leading by example dimension is proven to affect employee creativity. While the other four dimensions have no significant effect. The practical implication is that companies are expected to apply leadership that empowers employees and create programs to increase employee creative self-efficacy in an effort to increase employee creativity.